The phylogenetic nomenclature of ornithischian dinosaurs - Madzia, Daniel; Arbour, Victoria M.; Boyd, Clint A.; Farke, Andrew A.; Cruzado-Caballero, Penélope; Evans, David C. (PeerJ, 2021)
Ornithischians form a large clade of globally distributed Mesozoic dinosaurs, and represent one of their three major radiations. Throughout their evolutionary history, exceeding 134 million years, ornithischians evolved considerable morphological disparity, expressed especially through the cranial and osteodermal features of their most distinguishable representatives. The nearly two-century-long research history on ornithischians has resulted in the recognition of numerous diverse lineages, many of which have been named. Following the formative publications establishing the theoretical foundation of phylogenetic nomenclature throughout the 1980s and 1990s, many of the proposed names of ornithischian clades were provided with phylogenetic definitions. Some of these definitions have proven useful and have not been changed, beyond the way they were formulated, since their introduction. Some names, however, have multiple definitions, making their application ambiguous. Recent implementation of the International Code of Phylogenetic Nomenclature (ICPN, or PhyloCode) offers the opportunity to explore the utility of previously proposed definitions of established taxon names. Since the Articles of the ICPN are not to be applied retroactively, all phylogenetic definitions published prior to its implementation remain informal (and ineffective) in the light of the Code. Here, we revise the nomenclature of ornithischian dinosaur clades; we revisit 76 preexisting ornithischian clade names, review their recent and historical use, and formally establish their phylogenetic definitions. Additionally, we introduce five new clade names: two for robustly supported clades of later-diverging hadrosaurids and ceratopsians, one uniting heterodontosaurids and genasaurs, and two for clades of nodosaurids. Our study marks a key step towards a formal phylogenetic nomenclature of ornithischian dinosaurs.
Keywords: Phylogenetic nomenclature; Phylogenetic definition; PhyloCode; International Code of Phylogenetic Nomenclature; Ornithischia; Dinosauria